Assessing Tourist Loyalty: A Destination Analysis Approach For Beach Tourism In Batam City - Sihombing, Dame Afrina; Pertiwi, Intan Bahtera; Hariyanto, Oda Ignatius Besar (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Destination loyalty at Batam City Beach is influenced by place attachment and familiarity. Respondents who feel attached to the place and have a high sense of familiarity with the destination tend to have higher loyalty to the destination. This means that place attachment and familiarity has a positive impact on satisfaction, which then affects the level of destination loyalty. The research utilizes a quantitative method, gathering data through questionnaires evaluated on a Likert scale. The data was analyzed using SPSS software, and the statistical results revealed a positive and significant relationship between place attachment, familiarity, satisfaction, and destination loyalty for Batam City Beach. This indicates that the higher level of place attachment and familiarity, the higher level of satisfaction and destination loyalty. Results indicate that variables such as place attachment and familiarity influence destination loyalty, with satisfaction acting as a mediator. This research can serve as a reference for developing marketing strategies and enhancing destination loyalty at Batam City Beach.